A rare case of fundal rupture of uterus at term with placental blood supply from omental vessels in a tertiary care centre - S., Sunita; M. R., Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine rupture is one of the rare causes of obstetric hemorrhage with high incidence of fetal and maternal morbidity. The global prevalence of uterine rupture is 0.3-2.9%. The etiology for rupture in early decades was neglected labor, with passing years newer causes of uterine rupture have been added like previous cesarean delivery, uterine curettage, myomectomy, anomalies in uterus, etc. The most common site of uterine rupture is at the scar site of previous caesarean and the rupture may occur spontaneously or during labour, at the same time some unusual sites of rupture of uterus sparing the cesarean scar have also been documented in the world. We have incidentally detected a case of fundal rupture of uterus when we were performing emergency lower segment caesarean section for a term patient with previous lower segment caesarean delivery who came to us in labour without any imminent features of rupture. The rupture site was sealed by omentum and placenta was taking blood supply from omental vessels, there was no fresh bleeding from scar site. Omentum dissected from uterus, and rent was closed in two layers. Atonic PPH was encountered hence subtotal hysterectomy was done. The objective of this discussion is to raise awareness about the atypical appearance of uterine rupture and its consequences.